A molybdenum-doped bimetallic phosphide nanotube electrode material, a preparation method and application thereof
Patent Information
- Application Number
- CN202311756423.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-20
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2043-12-20
AI Technical Summary
[0008]本发明的目的是提供一种高效、稳定且具有纳米管状结构的HER/OER双功能催化电极材料以解决现有技术中存在的材料本征催化活性不够高,难以满足碱性电解水对高活性的需求,难以满足工业化碱性电解水对高稳定性的需求,以及在大电流密度下的传质特性和稳定性也不够理想的问题
[0029]1.本发明首次制备了三维自支撑钼掺杂双金属磷化物纳米管电极材料,通过合理的电子结构设计优化电化学水分解中间体的吸附自由能,有效激发了非贵金属基双功能催化剂的高活性,不仅具有优异的本征催化活性,而且具有高的电化学比表面积和快的传质特性,可在大电流密度下保持优异的传质特性和稳定性。
Smart Images

Figure CN117758301B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of nanotube electrode material synthesis and electrochemical technology application, specifically to a molybdenum-doped bimetallic phosphide nanotube electrode material, its preparation method, and its application. Background Technology
[0002] Currently, water electrolysis for hydrogen production is considered one of the most promising technologies for large-scale green hydrogen production. However, the use of extremely scarce Pt and Ir-based noble metal materials as the most effective cathode and anode catalysts for water electrolysis significantly hinders its efficient utilization. Therefore, there is an urgent need to develop efficient, stable, and low-cost non-noble metal-based catalytic materials for catalyzing the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER).
[0003] In recent years, 3d group non-noble metal transition metal phosphides have been considered promising water electrolysis catalysts due to their low cost and tunable electronic structure. However, most of them cannot serve as efficient bifunctional electrocatalysts for both HER and OER, leading to increased complexity in electrolyzer construction and reduced overall electrolysis efficiency. Therefore, increasing research is focused on exploring efficient basic HER and OER bifunctional catalysts. However, the use of non-noble metal-based catalysts for strongly basic reactions remains largely limited by the slow reaction kinetics at the cathode and anode interfaces. For HER, the slow water dissociation steps include the Volmer step (H₂O(aq) + e⁻)⁻. - →H ad + OH - ) and the Heyrovsky step (H2O(aq) + e - +H ad →H2 + OH - This significantly limits cathode activity. For OER, the slow four-electron transfer, accompanied by complex intermediate transformation processes, leads to very high overpotentials at the anode. Meanwhile, non-noble metal transition metal phosphides still face key challenges such as insufficient exposure of active sites, slow mass transfer, and catalyst activity reduction and detachment caused by the rapid collapse and bombardment of numerous bubbles generated on the catalyst surface at high current densities.
[0004] The patent document with patent number "CN202011645583.5" discloses "a method for preparing a nitrogen-doped porous carbon-encapsulated nickel-cobalt bimetallic phosphide nanorod array electrode", which includes the following steps: (1) growing NiCoCHH@NF material in situ on nickel foam; (2) immersing NiCoCHH@NF in a transparent solution formed by 2-methylimidazole and allowing it to stand at room temperature to obtain NiCo-MOFs@NF; (3) preparing carbon nanotube composite electrode material NiCoPx@NGC@NF in a tube furnace. The following problems exist:
[0005] 1. Because NiCo-based bimetallic phosphides lack efficient water dissociation sites, the intrinsic catalytic activity of the prepared materials is not high enough, making it difficult to meet the high activity requirements of alkaline water electrolysis; because nitrogen-doped porous carbon is used to coat the phosphides, the carbon materials are prone to oxidation and instability at high potentials in the OER reaction, making it difficult to meet the high stability requirements of industrial alkaline water electrolysis.
[0006] 2. Compared with nanotube array electrodes, nanorod array electrodes cannot fully expose more active sites and lack more efficient bubble mass transfer channels, resulting in less than ideal mass transfer characteristics and stability at high current densities.
[0007] Therefore, developing an economical, efficient, stable, and micro / nano / electronically tunable non-precious metal-based bifunctional catalyst is crucial for the performance and application of alkaline water electrolysis for hydrogen production. Summary of the Invention
[0008] The purpose of this invention is to provide a highly efficient, stable HER / OER bifunctional catalytic electrode material with a nanotube structure to solve the problems in the prior art, such as insufficient intrinsic catalytic activity, difficulty in meeting the high activity requirements of alkaline water electrolysis, difficulty in meeting the high stability requirements of industrial alkaline water electrolysis, and unsatisfactory mass transfer characteristics and stability at high current densities.
[0009] To achieve the objectives of this invention, the present invention provides the following technical solution: a method for preparing a self-supporting molybdenum-doped bimetallic phosphide nanotube electrode material, comprising the following steps:
[0010] (1) Preparation of precursor solution A and precursor solution B:
[0011] Equimolar amounts of NaMoO4·2H2O and NiCl2·6H2O were dispersed in a deionized aqueous solution and stirred for 10 min to 30 min. The mixture was then transferred to the inner liner of a hydrothermal reactor to obtain precursor solution A.
[0012] K3(Fe(CN)6) was dispersed in an aqueous solution and stirred for 10 to 30 minutes. The solution was then transferred to the inner liner of a hydrothermal reactor to obtain precursor solution B.
[0013] (2) Preparation of NiMoO4 / NF nanowire composite:
[0014] After cleaning and drying, nickel foam (NF) was placed in precursor solution A for hydrothermal reaction, cooled to room temperature, cleaned and dried to obtain NiMoO4 / NF nanowire composite.
[0015] (3) Preparation of nanotube composite material Mo-FeNi PBA NTs / NF:
[0016] The NiMoO4 / NF nanowire composite was placed in precursor solution B for hydrothermal reaction, cooled to room temperature, washed and dried for 6 h to 24 h to obtain the molybdenum-doped bimetallic iron-nickel Prussian blue analog nanotube composite Mo-FeNi PBA NTs / NF.
[0017] (4) Preparation of Mo-FeNiP NTs / NF composite electrode material:
[0018] NaH2PO2 powder and Mo-FeNiP NTs / NF samples were placed upstream and downstream of a dual-temperature zone tube furnace, respectively. The upstream and downstream temperature zones were heated to 260℃~300℃ and 300℃~400℃, respectively, under an inert gas atmosphere and held for 1-3 h. After cooling to room temperature, Mo-FeNiP NTs / NF composite electrode materials were obtained.
[0019] Furthermore, in step (1) above, the concentration of the mixed solution A is 0.017~0.042 mol / L, and the concentration of the mixed solution B is 0.017~0.042 mol / L.
[0020] Furthermore, in step (2) above, the nickel foam is cut into rectangles with a length of 2-5 cm and a width of 1-2 cm, and then placed into the precursor A solution.
[0021] Furthermore, in step (2) above, the hydrothermal reaction temperature is 120~200℃ and the hydrothermal reaction time is 5~24h.
[0022] Furthermore, in step (3) above, the hydrothermal reaction temperature is 60~130℃ and the hydrothermal reaction time is 2~12h.
[0023] Furthermore, in steps (2) and (3) above, the drying temperature is 50℃~80℃ and the drying time is 6h~24h.
[0024] Furthermore, in step (4) above, the inert gas is argon or nitrogen, and the phosphating heating rate in the downstream temperature zone is 2~10℃ / min.
[0025] Furthermore, the above preparation method yields a molybdenum-doped bimetallic phosphide nanotube electrode material.
[0026] Furthermore, the above-mentioned molybdenum-doped bimetallic phosphide nanotube electrode material is applied in the field of water electrolysis.
[0027] Furthermore, the application of the aforementioned molybdenum-doped bimetallic phosphide nanotube electrode material in the field of water electrolysis involves assembling an electrolytic cell using the composite electrode material directly as both the cathode and anode.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. This invention is the first to prepare a three-dimensional self-supporting molybdenum-doped bimetallic phosphide nanotube electrode material. By optimizing the adsorption free energy of the electrochemical water splitting intermediate through reasonable electronic structure design, the high activity of the non-noble metal-based bifunctional catalyst is effectively stimulated. It not only has excellent intrinsic catalytic activity, but also has high electrochemical specific surface area and fast mass transfer characteristics. It can maintain excellent mass transfer characteristics and stability under high current density.
[0030] 2. In the preparation process of this invention, the obtained NiMoO4 / NF nanowire composite is placed in a precursor solution B prepared with K3(Fe(CN)6), and hollow nanotubes are prepared through an ion exchange reaction, while simultaneously forming Mo-doped NiFe bimetallic phosphide. In this step, [Fe(CN)6] in the solution... 4− Ion-controlled etching of the NiMoO4 / NF nanowire surface leads to the formation of Prussian blue analogues with nanotubular structures due to the differences in inward and outward diffusion kinetics of different ions. The phosphating of these Prussian blue analogues not only effectively exposes the number of catalytically active sites but also facilitates electrolyte penetration and bubble transport, thus effectively enhancing the catalytic activity of the product of this invention.
[0031] 3. The non-precious metal sources such as Fe, Ni, and Mo used in this invention are characterized by low cost, low risk, and wide availability. Furthermore, the preparation method of this invention employs mild reaction conditions that are easy to control, simple to operate, low in cost, and have a short production cycle, making it easy to achieve large-scale industrial production.
[0032] 4. The three-dimensional self-supporting molybdenum-doped bimetallic phosphide nanotube electrode material prepared by this invention can be directly used as an electrode without the need for a binder. Due to its excellent bifunctional water electrolysis catalytic properties, it can be simultaneously used as both the cathode and anode in an alkaline electrolyzer, greatly simplifying the electrolyzer structure. Electrolyzers prepared using the material of this invention exhibit extremely low overpotential, high operating current density, and excellent cycle performance, effectively improving water electrolysis efficiency and reducing energy consumption, thus possessing significant application value in the field of hydrogen production through water electrolysis. Attached Figure Description
[0033] Figure 1 This is a TEM image of the molybdenum-doped bimetallic iron-nickel Prussian blue analog nanotube precursor prepared in Example 1.
[0034] Figure 2 The image shows the XRD pattern of the molybdenum-doped bimetallic iron-nickel phosphide nanotube / nickel foam composite electrode prepared in Example 1.
[0035] Figure 3This is a TEM image of the molybdenum-doped bimetallic iron-nickel phosphide nanotube / nickel foam composite electrode prepared in Example 1.
[0036] Figure 4 The graph shows the complete water desorption polarization curve of the molybdenum-doped bimetallic iron-nickel phosphide nanotube / nickel foam composite electrode prepared in Example 1.
[0037] Figure 5 The image shows the water-splitting stability test curve of the molybdenum-doped bimetallic iron-nickel phosphide nanotube / nickel foam composite electrode prepared in Example 1. Detailed Implementation
[0038] The present invention will now be described in detail with reference to the accompanying drawings and embodiments.
[0039] Example 1: A method for preparing a molybdenum-doped bimetallic phosphide nanotube electrode material, comprising the following steps:
[0040] (1) Preparation of precursor solution A and precursor solution B:
[0041] 2.5 mmol of NaMoO4·2H2O and 2.5 mmol of NiCl2·6H2O were dispersed in 60 mL of deionized water solution. After stirring magnetically at room temperature for 10 min, the solution was transferred to the inner liner of a hydrothermal reactor to obtain solution A.
[0042] 100 mg of K3(Fe(CN)6) powder was dispersed in 60 mL of aqueous solution and magnetically stirred at room temperature for 10 min. The solution was then transferred to the inner liner of a hydrothermal reactor to obtain solution B.
[0043] (2) Preparation of NiMoO4 / NF nanowire composite:
[0044] Nickel foam (NF) was cut into 2 cm × 5 cm rectangles, ultrasonically cleaned and dried with hydrochloric acid solution, water, and ethanol, and then placed in precursor solution A for hydrothermal reaction at 150 °C for 6 h. After cooling to room temperature, ultrasonically cleaned with water and ethanol, and dried at 60 °C for 24 h, NiMoO4 / NF nanowire composite was obtained.
[0045] (3) Preparation of nanotube composite material Mo-FeNi PBANTs / NF:
[0046] The NiMoO4 / NF nanowire composite was placed in precursor solution B and hydrothermally reacted at 80℃ for 2 h. After cooling to room temperature, it was ultrasonically cleaned with water and ethanol, and then dried at 60℃ for 24 h to obtain the molybdenum-doped bimetallic iron-nickel Prussian blue analog nanotube composite Mo-FeNi PBA NTs / NF.
[0047] (4) Preparation of Mo-FeNiP NTs / NF composite electrode material:
[0048] One g of NaH₂PO₂ powder and a 2 cm × 5 cm Mo-FeNi PBA NTs / NF sample were placed upstream and downstream of a dual-temperature zone tube furnace, respectively. The upstream and downstream zones were then heated to 280 °C and 350 °C, respectively, under a high-purity argon atmosphere and held for 2 h. After cooling to room temperature, a highly efficient and stable molybdenum-doped bimetallic iron-nickel phosphide nanotube / nickel foam composite electrode material was obtained.
[0049] Examples 2-5: The preparation steps are the same as in Example 1, except for the different amounts of raw materials and process parameters, as detailed in Table 1.
[0050] Of the above embodiments, Embodiment 1 is the preferred embodiment:
[0051] Depend on Figure 1 It can be seen that the XRD pattern of the molybdenum-doped bimetallic iron-nickel phosphide nanotube / nickel foam composite electrode material prepared in Example 1, except for the nickel foam substrate peak, shows that the remaining diffraction peaks match the Ni2P standard card, indicating that the composite electrode material is a metal phosphide.
[0052] Depend on Figure 2 As can be seen, in the preparation process of Example 1, the present invention utilizes [Fe(CN)6] in solution. 4− Ion-controlled etching of the NiMoO4 / NF nanowire surface resulted in the formation of Prussian blue analogues with nanotubular structures due to the differences in diffusion kinetics between different ions inward and outward.
[0053] Depend on Figure 3 It is known that the molybdenum-doped bimetallic iron-nickel phosphide nanotube / foam nickel composite electrode material prepared by the present invention inherits the hollow nanotube structure of the Prussian blue analog precursor, which can not only effectively expose the number of catalytic active sites, but also facilitate the penetration of electrolyte and the transport of bubbles.
[0054] The self-supporting molybdenum-doped bimetallic iron-nickel phosphide nanotube / nickel foam composite electrode material obtained in Example 1 was directly used as the cathode and anode to assemble an electrolytic cell. The electrode area was selected as 1 cm × 1 cm, and the electrolyte was 1 mol L⁻¹. -1 The assembled electrolytic cell was tested at room temperature using a KOH solution, and the test results are as follows. Figure 4 , Figure 5 As shown:
[0055] Depend on Figure 4It can be seen that the electrolytic cell assembled using the molybdenum-doped bimetallic iron-nickel phosphide nanotube / nickel foam composite electrode prepared in Example 1 of this invention as both cathode and anode only requires a voltage of 1.47 V to achieve 10 mA cm⁻¹. -2 The current density is much lower than that of an electrolytic cell assembled with RuO2 as the anode and Pt / C as the cathode (1.57 V), indicating that the molybdenum-doped bimetallic iron-nickel phosphide nanotube / nickel foam composite electrode prepared in this invention is a highly efficient bifunctional catalyst.
[0056] Depend on Figure 5 It can be seen that the electrolytic cell assembled using the molybdenum-doped bimetallic iron-nickel phosphide nanotube / nickel foam composite electrode prepared in Example 1 of this invention, at a current density of 100 mA / cm², achieves optimal performance. 2 Under certain conditions, it can maintain a stable cycle for 100 hours, demonstrating high cyclic stability.
[0057] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention shall still fall within the protection scope of the present invention.
Claims
1. A method for preparing a self-supporting molybdenum-doped bimetallic phosphide nanotube electrode material, characterized in that: Includes the following steps: (1) Preparation of precursor solution A and precursor solution B: Equimolar amounts of NaMoO4·2H2O and NiCl2·6H2O were dispersed in a deionized aqueous solution and stirred for 10 to 30 minutes. The mixture was then transferred to the inner liner of a hydrothermal reactor to obtain precursor solution A, which had a concentration of 0.017 to 0.042 mol / L. K3(Fe(CN)6) was dispersed in an aqueous solution and stirred for 10 to 30 minutes. The solution was then transferred to the inner liner of a hydrothermal reactor to obtain precursor solution B, which had a concentration of 0.017 to 0.042 mol / L. (2) Preparation of NiMoO4 / NF nanowire composite: After cleaning and drying, nickel foam (NF) was placed in precursor solution A for hydrothermal reaction, cooled to room temperature, cleaned and dried to obtain NiMoO4 / NF nanowire composite. The hydrothermal reaction temperature is 120~200℃, and the hydrothermal reaction time is 5~24h; (3) Preparation of nanotube composite material Mo-FeNi PBA NTs / NF: The NiMoO4 / NF nanowire composite was placed in precursor solution B for hydrothermal reaction, cooled to room temperature, washed and dried for 6 h to 24 h to obtain the molybdenum-doped bimetallic iron-nickel Prussian blue analog nanotube composite Mo-FeNi PBA NTs / NF. The hydrothermal reaction temperature is 60~130℃, and the hydrothermal reaction time is 2~12h; (4) Preparation of Mo-FeNiP NTs / NF composite electrode material: NaH2PO2 powder and Mo-FeNiP NTs / NF samples were placed upstream and downstream of a dual-temperature zone tube furnace, respectively. The upstream and downstream temperature zones were heated to 260℃~300℃ and 300℃~400℃, respectively, under an inert gas atmosphere and held for 1-3 hours. After cooling to room temperature, Mo-FeNiP NTs / NF composite electrode materials were obtained.
2. The method for preparing a self-supporting molybdenum-doped bimetallic phosphide nanotube electrode material according to claim 1, characterized in that: In step (2), the nickel foam is cut into rectangles with a length of 2-5 cm and a width of 1-2 cm, and then placed into the precursor A solution.
3. The method for preparing a self-supporting molybdenum-doped bimetallic phosphide nanotube electrode material according to claim 1 or 2, characterized in that: In steps (2) and (3), the drying temperature is 50℃~80℃ and the drying time is 6h~24h.
4. The method for preparing a self-supporting molybdenum-doped bimetallic phosphide nanotube electrode material according to claim 3, characterized in that: In step (4), the inert gas is argon or nitrogen, and the phosphating heating rate in the downstream temperature zone is 2~10℃ / min.
5. A molybdenum-doped bimetallic phosphide nanotube electrode material prepared by the preparation method according to claim 1.
6. The application of the molybdenum-doped bimetallic phosphide nanotube electrode material prepared by the method according to claim 5 in the field of water electrolysis.
7. The application of the self-supporting molybdenum-doped bimetallic phosphide nanotube electrode material according to claim 6 in the field of water electrolysis, characterized in that: It involves assembling an electrolytic cell by directly using composite electrode materials as both the cathode and anode.
Citation Information
Patent Citations
Preparation method of nitrogen-doped porous carbon-coated nickel-cobalt bimetallic phosphide nano rod array electrode
CN112708906A